Thermo-Chemical Treatment for Carcass Disposal and the Application of Treated Carcass as Compost - Jae-In Lee; Eun-Ji Cho; Fritz Ndumbe Lyonga; Chang-Hee Lee; Sue-Yun Hwang; Dock-Hwan Kim; Chang-Gu Lee; Seong-Jik Park (Applied Sciences, 2021)
A mechanized thermo-chemical treatment system was developed to treat the undecomposed carcass and remediate livestock burial sites. Animal carcasses were thus processed via crushing, mixing, and treatment with quicklime treatment, heat treatment (200–500 °C), and mixing with sawdust. The machinery was applied to two sites where 16,000 chickens and 418 pigs had previously been buried in fiber-reinforced plastic storage bins. No dioxins were detected in the gas discharged during processing, and the concentration of total volatile organic compound, toluene, ethylbenzene, xylene, and styrene were 430.3, 139.0, 18.3, 21.4, and 10.4 μg/m3, respectively, which were below the air pollutant emission standards issued by the Korean Ministry of Environment. Korean standards stipulating the use of treated carcasses as compost (C, N, and P content, heavy metal concentration, Escherichia coli, and Salmonella) were met, but the germination index value was less than 70, not satisfying the criteria. Plant height, leaf length, leaf width, and dry weight of lettuce grown in soil amended with treated carcass product were significantly lower than those grown in low nutrient soil due to the poor germination index of the treated carcass. These results indicate that a composting process is required before the use of the treated carcass as a fertilizer. The addition of zeolite retarded the elution of ammonia from the carcasses and its efficiency was about 87.9%. It is expected that the mechanized thermo-chemical treatment process developed in this study could replace other technologies for the remediation of livestock burial sites.